Kajian Linguistik tentang Campur Kode dalam Konten YouTube Livy Renata: Studi Kasus "Who Knows Me Better Yasuke VS Jerome!" - Linda Rofi Saumi; Eva Mazidah (Jurnal Studi Multidisiplin Qomaruna, 2026)
The phenomenon of code-mixing has become increasingly common on social media platforms such as YouTube, where creators engage audiences from diverse linguistic and cultural backgrounds. This study addresses the limited research on the specific forms of code-mixing employed by Indonesian YouTubers, focusing on Livy Renata. This study aims to identify and classify the types of code-mixing used in her YouTube content. Using Muysken’s (2000) theoretical framework, this study analyzed language data from a selected video on Livy Renata’s channel. A descriptive qualitative method was applied to examine the occurrences and types of code mixing present. The analysis identified 47 code-mixing instances, comprising 16 insertions (34%), 24 alternations (51%), and 7 congruent lexicalizations (15%). These findings suggest that alternation is the most dominant form of code-mixing in this context, reflecting a flexible linguistic strategy influenced by bilingual interactions. This study provides insights into how Indonesian content creators navigate multilingual communication, contributing to broader sociolinguistic discussions on digital code-mixing practices.